Is adding resources always beneficial? Multiplicative impact of psychological capital and goal-oriented climate on Spanish public worker satisfaction and engagement - Díaz-Fúnez, Pedro Antonio; Cardella, Giuseppina María; Hernández-Sánchez, Brizeida Raquel; Sánchez-García, José Carlos; Mañas-Rodríguez, Miguel Ángel (Frontiers in Psychology, 2024)
Introduction The motivation process from personal resources to commitment of administrative employees is still little studied. This article uses the Job Demands-Resources model to investigate how the multiplicative effect of personal resources and a goal-oriented climate among public employees influences their satisfaction and engagement at work. Specifically, it proposes a model where the influence of psychological capital on engagement is mediated by job satisfaction and moderated by the goal orientation climate. Method A total of 326 employees of the administrative staff of a Spanish Public Administration answered a self-reported survey. Partial Least Square-Structural Equation Modeling (PLS-SEM) approach was used to evaluate the validity and reliability of the data, as well as, to test the hypotheses formulated. Results The SEM results show the positive impact of psychological capital on employee engagement, and the mediating role of job satisfaction in this relationship. Furthermore, the existence of a goal-oriented climate negatively moderated the relationship between Psychological Capital and Job Satisfaction, reducing the mediation effect. Discussion These findings open new doors for future research in the necessary adaptation of human resource policies to improve the motivation process in the public administration context.